SLEEP PRACTICES OF FAMILY CAREGIVERS: FINDINGS FROM THE FAMTECHCARE STUDY. (11th November 2018) - Kim, S; Williams, K; Shaw, C; Perkhounkova, E; Blyler, D; Hein, M; Seabold, D
Abstract: BACKGROUND Currently, 15.2 million caregivers provide care for a person with dementia (PWD) and experience stress, strain, and burden that contribute to insomnia and other negative sleep outcomes. FamTechCare is a telehealth intervention that uses in-home video recordings to link family caregivers to experts for individualized guidance in managing care. In this analysis, we examined baseline characteristics of participating caregivers and PWD in relation to self-reported baseline sleep measures using the Pittsburg Sleep Quality Index. METHODS Bivariate relationships between demographic factors for caregivers (N = 92) and PWD (N = 73) and self-reported caregiver sleep practices were investigated using Mann-Whitney U or Fisher's exact test. Multiple logistic regression was used to identify explanatory variables for sleep disturbance, latency, and day time dysfunction related to sleep. RESULTS Most caregivers (61%) reported sleeping at least 7 hours per night, while 17% slept less than 6 hours. Every fourth caregiver reportedly used sleep medications at least once a week. Caregivers of male PWDs tended to sleep longer (p = .01). Caregivers of married male PWDs reported more sleep disturbance than caregivers of single PWDs (p=.02). Older age of caregivers was associated with less time to fall asleep (p=.01) and daytime dysfunction related to sleep (p = .03). Daytime dysfunction was also associated with caregivers being Black (p = .03). DISCUSSION Understanding factors associated with sleep issues for family caregivers of PWD, may help providers to address specific sleep issues that relate to caregiver characteristics.